If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+2x+2=2(3x+2)
We move all terms to the left:
4x+2x+2-(2(3x+2))=0
We add all the numbers together, and all the variables
6x-(2(3x+2))+2=0
We calculate terms in parentheses: -(2(3x+2)), so:We get rid of parentheses
2(3x+2)
We multiply parentheses
6x+4
Back to the equation:
-(6x+4)
6x-6x-4+2=0
We add all the numbers together, and all the variables
-2!=0
There is no solution for this equation
| 9(x−3)+3x=7x+43 | | 30=-5(2n+8) | | 2x+10=8x-4 | | 5x²-2=78 | | -7(6x-3)=20 | | 6x+2=-26-8x | | 12+4v=3v+5 | | q2− 1=1.5 | | (x+5)(x+12)=18 | | x/9-14=22 | | -8d=-8-9d | | 6n-32=4(1-3n) | | 5(y-4)=7(2y-1 | | 8x–20=5x+4 | | x÷9-14=22 | | 3(x-3)-5=19 | | 13x-2=12x+7+2 | | 8x+2=-18+x | | -5(1+4m)=-8+4m | | 2x+3(5=2x)+3 | | -12x+10=42x-10 | | -5x+5=4x-13 | | x+x+2+3x-6=31x+x+2+3x−6=31 | | 65+10x=35-5x | | -3x18=7x | | 17x=8=22x-7 | | 6(2-v)-v=2(v+1) | | 2)22=1+8a+5 | | 2(3n+1.5)=5(n–4) | | 15-9(2x+3)=-16x+40 | | 3(x-2)=2x-4+x-1 | | 10y+19.95=139.96 |